Mental health problems in children with prader-willi syndrome. - Gallagher, Louise; Meehan, Judith (My University, 2012)
BACKGROUND: Prader-Willi Syndrome (PWS) is a genetically determined neurodevelopmental disorder, which occurs in approximately one in 22000 births. AIMS: This study aimed to investigate psychiatric characteristics of children diagnosed with PWS compared with an age-, gender- and IQ-matched control group. The parents of children with PWS were assessed for psychological distress in comparison to the parents of the control group. Methodological limitations identified in previous studies were addressed in the present study. METHODS: Psychiatric problems were evaluated in a sample of children with genetically confirmed PWS and an age- and IQ-matched control group using the Child Behaviour Checklist 6-18. Parental psychological distress for both groups was evaluated with the Brief Symptom Inventory. RESULTS: Children with PWS had more severe somatic, social, and thought problems, and were more withdrawn-depressed in comparison to controls. Borderline difficulties were detected for the affective, somatic, and attention deficit-hyperactivity CBCL DSM-orientated subscales in the PWS group. Parents of PWS children, in comparison to controls, had more somatization, phobic anxiety, obsessive-compulsive, and anxiety problems. CONCLUSIONS: PWS represents a complex psychological disorder with multiple areas of disturbances
PUBLISHED
Keywords: Psychiatry